ANALYSIS OF CONSUMER SATISFACTION WITH PERFORMANCE OF PROPERTY DEVELOPERS - Pertiwi, Andicka; Sya’roni, Deden A. Wahab (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research aims to determine the level of consumer satisfaction with the performance of property developers in the Mulyahurip Anugrah Persada Sumedang housing complex based on security and comfort, electricity and water facilities, building design, company services and selling prices. Respondents were selected using the Slovin formula, the number of residents of the Mulyahurip Anugrah Persada housing complex was 124 families, while the number of respondents was 55 families. The data was analyzed using quantitative analysis, then the data was processed to find the average nominal score using the MS.excel program. This research was analyzed using nine available attributes with five nominal score assessments. The results of consumer satisfaction research at Mulyahurip Anugrah Persada Sumedang Housing on nine attributes show that performance is in accordance with the wishes of residents and the wishes of residents are said to be very satisfied.